Design Of Hybrid RF Diplexer And Triplexer For Multiband WiMAX Application - Sazali, Muhammad Aizat (2018)
Radio frequency (RF) diplexer and triplexer are widely used in wireless communication system. The development of RF diplexer and triplexer are very competing in multiband Worldwide Interoperability for Microwave Access (WiMAX) application. This is due to the high demands of wireless communication system to support multi-services simultaneously. Many RF diplexer and triplexer are designed using common type of the filter. Besides, the preliminary designs are for multi-applications not specifically for multiband WiMAX application. The multiband WiMAX has been implemented around the globe as allocated by the International Telecommunication Union (ITU). Bandwidth of the multiband WiMAX application are varies depending on the countries. Therefore, the proposed RF diplexer and triplexer are developed to cope with the multiband WiMAX bandwidth. This is because of the bandwidth is purposely to allow the data to be transmitted or received based on the frequencies assigned. The proposed RF diplexer and triplexer were designed with three different resonators as to cover the multiband WiMAX bandwidth which were at 2.3, 2.6 and 3.5 GHz. The resonator types were selected based on the bandwidth achieved by the resonator. In addition, the resonators used were based on the coupled lines technique on a microstrip structure due to the flexibility during development processes such as open loop, parallel and folded structures. The proposed RF diplexer and triplexer are based on the hybrid structure which more flexible for the resonators to match with the matching network. By synthesis and analysis on the overall performances of the proposed RF diplexer and triplexer, the specific bandwidths were achieved for multiband WiMAX application. Results showed that the resonators produced bandwidths of I 00 MHz for the narrow band with minimum 4 % fractional bandwidth, and 200 to 700 MHz with 10 - 20 % fractional bandwidth for the moderate band. These results showed that the resonators were achieved good agreements to be implemented in multiband WiMAX application.